Já não vale a pena ir para lá: The changing discourse on migration to South Africa by Mozambicans - Machele, Julio (Southern Journal for Contemporary History, 2022)
Even though for decades poems and songs criticised Mozambicans’ migratory work in South Africa, many young people from southern Mozambique still saw the work on plantations, mines and other paid occupations in South Africa as a way to be freed from the heavy burdens of marrying and raising a family and at the same time as a chance to accumulate wealth. However, in recent years the “fears” conveyed in poetry, songs, and other literary forms have gained prominence. Many Mozambicans with work experience in South Africa now point out that, “it is no longer worth going there”. By discouraging other Mozambicans from considering South Africa the “golden metropolis”, they adopt a discursive shift that is partly the result of new conjunctures, both in Mozambique and South Africa. This article aims to show that some poets and musicians have appropriated and reinterpreted the migratory work of Mozambicans in South Africa, emphasising more the negative aspects, thus contradicting the contemporary hegemonic discourse which saw migratory work in South Africa as the salvation for young and adult men. I examine, in particular, the works of José João Craveirinha. I argue that his position on migratory work is an extension of his anti-colonial struggle, which started in the 1950s. I also look at other songs by different authors who interpret migratory work based on their colonial and postcolonial experiences. I highlight that, in recent years, these critical voices tend to be taken up by people with or without experience of migratory work in South Africa to discourage further migration. Finally, I point out the poet’s and the musicians’ silences regarding Mozambican women’s migratory work in South Africa and simultaneously emphasise that women have always been discouraged from migrating. The poet and the musicians only had eyes for the local South African prostitutes who enticed Mozambican men, gave them venereal diseases and made them forget their wives and families in Mozambique.